(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
Taxes and Fiscal Pressure in Acapulco, 1777-1809 analyses the intricate world of private local interests, the complicated government officials’ family nets and their deep corruption. José de Gálvez’s arrival to New Spain as a general supervisor allowed people to know about some cases of corruption like the one Viceroy Marquis de Cruillas was involved in through his nephew Fernando de Monserrat, governor of Acapulco, who was benefited by commercial activities without paying taxes or by illegal trade. From that moment on Gálvez finished the Viceroy’s corrupted career and he started drastic political and administrative innovations. He ordered trade regulations with Asia be applied, He punished the Authorities involved in misconduct and he took measures to stop fraud against the Royal Treasury Office. The article also studies the various forms of resistance that these measures broke out, the main local outlaws and their accomplices in Mexico City